Plasma calcitonin gene‐related peptide (CGRP) in migraine and endometriosis during the menstrual cycle. Issue 6 (2nd May 2021) - Raffaelli, Bianca; Overeem, Lucas Hendrik; Mecklenburg, Jasper; Hofacker, Maxi Dana; Knoth, Henriette; Nowak, Claus Peter; Neeb, Lars; Ebert, Andreas Dietmar; Sehouli, Jalid; Mechsner, Sylvia; Reuter, Uwe
Abstract: Objective: Migraine, endometriosis, and the comorbidity of both are frequent pain disorders of special relevance for women. The neuropeptide calcitonin gene‐related peptide (CGRP) is critically involved in migraine, and circumstantial evidence suggests a role in endometriosis. We assessed CGRP levels at different times of menstrual cycle in four groups: healthy women, women with migraine or endometriosis and with the comorbidity of both. Methods: Women with episodic migraine and women with a histologically confirmed endometriosis were recruited from specialized centers. For CGRP determination with a commercial enzyme immunoassay kit, cubital vein blood samples were collected on menstrual cycle day 2 ± 2 (during menstruation) and on day 15 ± 2 (periovulatory period). The primary endpoint of the study was the absolute difference of CGRP plasma levels between the menstrual and the periovulatory phase of all study groups. Groups were compared using nonparametric test procedures. Results: A total of 124 women were included in the study. The change of CGRP plasma levels between menstruation and the periovulatory period was different between groups ( p = 0.007). Women with comorbid migraine and endometriosis showed an increase of CGRP in the menstrual phase of +6.32 (interquartile range, IQR −3.64–13.60) compared to the periovulatory time, while healthy controls had a decrease of −10.14 (−22.54–0.91, p = 0.004). CGRP levels were different in the periovulatory phase among groups ( p = 0.008), with highest values in healthy controls. Interpretation: CGRP levels change significantly during the menstrual cycle. Different patterns in women with the comorbidity point to a deviant regulation of CGRP release.